1979
DOI: 10.1002/pssa.2210520109
|View full text |Cite
|
Sign up to set email alerts
|

Application of high-density current in plastic working of metals

Abstract: Es wird ebenfalls gezeigt, daB die gemeinsame Wirkung von Ultraschall-und elektrischen Stromen es ermoglicht, Wolfram durch eine einzige Reduktion zu einem Grad zu deformieren, der als Rekord gelten kann, 85% oder dariiber. Insbesondere 1aBt sich ein Draht yon 0,41 mm Dnrchmesser in einem einzigen Durchgang zu einem flachen Band von 70 pm Dicke auswalzen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The effect of pulsed electric current on the relaxation of RS has previously been discussed widely in the literature [35,36]. It has been reported that stress relaxation and redistribution take place when the electric current density exceeds some threshold value, which varies depending on the metal/alloy used and is in the range of 10 8 to 10 9 A/m 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of pulsed electric current on the relaxation of RS has previously been discussed widely in the literature [35,36]. It has been reported that stress relaxation and redistribution take place when the electric current density exceeds some threshold value, which varies depending on the metal/alloy used and is in the range of 10 8 to 10 9 A/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The alternating magnetic treatment was accompanied by changes in magnetic field direction and in magnetic polarity and had a non-thermal effect on the two alloys, leading to dislocation depinning and increased mobility of dislocations, giving rise to an increase in the compressive stresses [36].…”
mentioning
confidence: 99%
“…Such verification has not been performed yet to our knowledge, but there is experimental evidence of plasticity increase under low temperature subthreshold electron or gamma irradiation, which has been discovered in early sixties [7] and investigated extensively thereafter (see e.g., [8]). Single crystals of Zn, Sn, In and Pb have been irradiated at liquid nitrogen temperature (78 K) with electron flux density ranging from 10 17 to 10 18 m À2 s À1 and energies below and above the threshold displacement energies, the latter being 0.7 MeV (Zn), 0.8 MeV (Sn, In) and 1.2 MeV (Pb).…”
Section: Irradiation-induced Dislocation Climb and Glidementioning
confidence: 99%
“…Defects formed under irradiation in the bulk act as additional pinning centers resulting in the well-known effect of radiation-induced hardening. On the other hand, there is less known but well established effect of the increase in plasticity of metals under sub-threshold irradiation [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…9a which would prevent the dislocation slipping. According to Troitskii et al [16,17], the drift electrons collide with the dislocations when the electric current is supplied on the sheet which can generate electron wind force in the metal. As shown in Fig.…”
Section: Influence Of Electric Current On Mechanism Of Ta15 Alloy Supmentioning
confidence: 99%